Influence of Online Learning on the Level of Inquisitiveness of Higher Secondary School Students - Rani, B. (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
"The important thing is not to stop questioning. Curiosity has its own reason for existing." -- Albert EinsteinLearning is what we humans do best. We learn throughout our lives by wondering and exploring, experiencing and playing. Online learning is education that takes place over the Internet. It is often referred to as “e- learning” among other terms. However, online learning is just one type of “distance learning” - the umbrella term for any learning that takes place across distance and not in a traditional classroom. Education may have several purposes, and online courses help to fulfill it. Some even say that e-learning can revolutionize education as it provides new opportunities for traditional learning. A curious person as inquisitive, questioning, probing, eager to learn, a sponge for information/ knowledge. If the person is interested in things, might say they are “inquisitive” or “dedicated to learning.” Generally, students are showing huge inquisitiveness in online learning. The present study is an attempt to find out the influence of online learning on the level of inquisitiveness of higher secondary school students. The sample of the study consisted of higher secondary students of Thiruvananthapuram district. A 3-point rating scale was prepared by the investigator for collecting the scores. It includes 30 statement It consist of three different areas and ten questions from each part. The different dimensions of inquisitiveness are imagination power, deeper thinking and curiosity.
Keywords: Online learning; Inquisitiveness; Higher secondary school students